Effects of the Infusion of 4% or 20% Human Serum Albumin on the Skeletal Muscle Microcirculation in Endotoxemic Rats - Damiani, Elisa (PLoS One, 2016)
BACKGROUND: Sepsis-induced microcirculatory alterations contribute to tissue hypoxia and organ dysfunction. In addition to its plasma volume expanding activity, human serum albumin (HSA) has anti-oxidant and anti-inflammatory properties and may have a protective role in the microcirculation during sepsis. The concentration of HSA infused may influence these effects. We compared the microcirculatory effects of the infusion of 4% and 20% HSA in an experimental model of sepsis. METHODS: Adult male Wistar rats were equipped with arterial and venous catheters and received an intravenous infusion of lipopolysaccharide (LPS, serotype O127:B8, 10 mg/kg over 30 minutes) or vehicle (SHAM, n = 6). Two hours later, endotoxemic animals were randomized to receive 10 mL/kg of either 4% HSA (LPS+4%HSA, n = 6), 20% HSA (LPS+20%HSA, n = 6) or 0.9% NaCl (LPS+0.9%NaCl, n = 6). No fluids were given to an additional 6 animals (LPS). Vessel density and perfusion were assessed in the skeletal muscle microcirculation with sidestream dark field videomicroscopy at baseline (t0), 2 hours after LPS injection (t1), after HSA infusion (t2) and 1 hour later (t3). The mean arterial pressure (MAP) and heart rate were recorded. Serum endothelin-1 was measured at t2. RESULTS: MAP was stable over time in all groups. The microcirculatory parameters were significantly altered in endotoxemic animals at t1. The infusion of both 4% and 20% HSA similarly increased the perfused vessel density and blood flow velocity and decreased the flow heterogeneity to control values. Microvascular perfusion was preserved in the LPS+20%HSA group at t3, whereas alterations reappeared in the LPS+4%HSA group. CONCLUSIONS: In a rat model of normotensive endotoxemia, the infusion of 4% or 20% HSA produced a similar acute improvement in the microvascular perfusion in otherwise unresuscitated animals.